Unveiling the Dynamic Connection: How Work Motivation Shapes the Pulse of Your Work Environment - Insights from the Pharma Horizon - Pitaloka, Endang; Avianti, Widiya (Universitas Pasundan, 2024)
In today's competitive business environment, organizations strive to enhance the performance of their employees in order to achieve their goals and gain a competitive edge. In this study, we aimed to investigate the impact of work motivation and the work environment on employee performance at PT XYZ. Our method of choice was quantitative, with employee performance as the dependent variable and work motivation style and work environment as independent variables. To gather data, we issued a questionnaire to 53 workers at PT XYZ and subsequently analyzed the data using IBM SPSS and the multiple linear regression analysis method. Upon processing validity and reliability tests, we conducted hypothesis testing and found that work motivation has a positive and significant effect on employee performance. However, the work environment was found to not be significant on its own, but it still exhibited a positive impact on employee performance. These results provide valuable insights for organizations looking to improve employee performance, suggesting that focusing on work motivation can yield significant benefits. On the other hand, while the work environment may not be directly significant, its positive impact indicates that it should not be overlooked in efforts to enhance employee performance. In conclusion, these findings shed light on the importance of understanding and cultivating work motivation in the workplace, while also emphasizing the supportive role of a positive work environment.